Method for extracting lithium from electrolytic aluminum waste through ultrasonic strengthening
Patent Information
- Application Number
- CN202411750554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The lithium leaching rate in the existing electrolytic aluminum scrap extraction process is low, the environment is unfriendly, and the lithium recovery rate is limited by the waste components of high alumina and high carbon.
Ultrasonic enhancement technology is used to process electrolytic aluminum waste during sulfuric acid leaching, combined with high-temperature calcination to remove carbon, two stages of impurity removal and low-temperature crystallization and denitrification, and finally, battery-grade lithium carbonate is obtained through sodium carbonate precipitation and CO2 gas treatment.
It significantly improves the leaching rate and recovery rate of lithium, reduces the processing cost and environmental impact, simplifies the process flow, and improves the economic benefits of lithium extraction.
Smart Images

Figure CN119612557A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of extraction and utilization of lithium-containing waste from electrolytic aluminum, and in particular to a method for ultrasonic enhanced lithium extraction from electrolytic aluminum waste. Background Art
[0002] In recent years, with the rapid development of new energy in my country, the industrialization of related industries such as electric vehicles and energy storage industries is in full swing. The country has also introduced a series of policies to encourage development. my country's new energy industry is not only technologically advanced and large-scale, but has also expanded its industry to other countries and regions such as Europe and the United States, leading the world. The development of the new energy industry has also driven the layout of lithium resources and the development and continuous improvement of lithium extraction technology.
[0003] The demand for lithium in the new energy industry has increased dramatically, prompting countries around the world to develop and plan the extraction of various lithium resources. my country is a major producer of electrolytic aluminum in the world. Waste materials such as aluminum ash produced in the electrolytic aluminum process also contain some lithium and a large amount of aluminum. Due to the rise in lithium prices in recent years, a number of lithium battery recycling companies have carried out research on the extraction and utilization technology of lithium in aluminum slag, and carried out industrial layout to obtain more cheap lithium resources. At the same time, waste materials are recycled to alleviate the shortage of lithium resources.
[0004] For example, the Chinese patent application number 2023107040418 discloses a process for improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, which comprises the following steps: preparing 10L of 5% aluminum chloride solution, adding 10g of waste slag to every 100ml of aluminum chloride solution, adding 1kg of waste slag to control the end point pH value to 3, leaching for 2 hours at room temperature, filtering and washing the filter residue, the filter residue is mainly impurities such as carbon, and the filtrate enters the impurity removal enrichment and purification process. The present invention uses an aluminum salt solution to dissolve the lithium sodium cryolite in the difficult-to-leach aluminum electrolytic waste slag, so that the lithium therein can be converted into lithium chloride or lithium sulfate, etc., thereby improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, and effectively solving the problem of low lithium leaching rate and environmental unfriendly in the existing recovery process. However, this method uses aluminum chloride as a dissolving medium, the concentration of lithium in the leachate is low, and the leachate contains extremely high aluminum. Although the lithium leaching rate is high, it affects the recovery of lithium.
[0005] In addition, for the electrolytic aluminum waste slag with very high sodium and aluminum content and nearly half carbon, the amount of sulfuric acid and sodium hydroxide required to extract all the aluminum and lithium is very large, the amount of sodium sulfate crystallization is large, and the precipitation and filtration properties are poor, which affects the total recovery rate of lithium. Therefore, it is necessary to develop a simpler, more economical and more effective method for extracting lithium from electrolytic aluminum slag to solve the above problems. Summary of the invention
[0006] Therefore, in order to solve the problems existing in the prior art, the present invention provides a method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement, which specifically comprises the following steps:
[0007] Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content;
[0008] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of no more than 80 meshes to obtain a decarbonized material;
[0009] Step 3: Leach the decarbonized material with sulfuric acid. During the sulfuric acid leaching process, the material is subjected to ultrasonic vibration and mechanical stirring. An ultrasonic generator is installed in the ultrasonic enhanced kettle. The power of the ultrasonic generator is 500-2000W. After the material is slurried, ultrasonic enhanced leaching is performed in the kettle. The leaching pH value is adjusted to 3.0-4.0, the ultrasonic power is 500-2000W, and the leaching liquid and leaching residue are obtained after filtration; the ultrasonic enhanced kettle is connected to the absorption device. The absorption liquid in the absorption device is a dilute alkali solution to absorb the fluorine and acid mist generated during the leaching process;
[0010] Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the second stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, filtering to obtain a lithium-containing filtrate and an impurity filter residue;
[0011] Step 5: The lithium-containing filtrate is heated and concentrated, and then subjected to a freezing crystallization step to obtain a denitrified liquid;
[0012] Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate;
[0013] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
[0014] Furthermore, the composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 12.5-12.8%, sodium 11.5-11.9%, iron 0.8-0.9%, calcium 1.8-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
[0015] Furthermore, the size of the electrolytic aluminum waste after crushing in step 1 is 1-10 cm.
[0016] Furthermore, in step 3, the slurry liquid-solid ratio of water to carbon removal material in the leaching process is 3-5:1, the sulfuric acid is 98% sulfuric acid, the leaching temperature is 60-90° C., and the leaching time is 1-3 hours.
[0017] Furthermore, in step 4, the oxidant in the first impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, and oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
[0018] Furthermore, the temperature of the freezing crystallization in step 5 is -10°C to 10°C.
[0019] Furthermore, the heating temperature in step 6 is 90-100°C.
[0020] Furthermore, in step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2 MPa.
[0021] Furthermore, the temperature of the heating crystallization in step 7 is 90-100°C.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The electrolytic aluminum waste of the present invention is first calcined or burned to remove most of the carbon therein, so that the lithium extraction processing capacity can be increased by almost one-fold, and the concentration of the lithium solution can be increased by about one-fold, which greatly reduces the processing difficulty and cost and improves the lithium recovery rate and processing efficiency.
[0024] (2) The present invention controls the pH value of the leaching process to 3.0-4.0, within which range the lithium in the electrolytic aluminum waste is dissolved, while most of the aluminum, iron, sodium, fluorine, etc. are not dissolved and remain in the leaching residue, thereby reducing the amount of leaching acid used and greatly reducing the amount of alkali used for impurity removal. The slag filtering performance is good, and the sodium content in the lithium solution is greatly reduced after impurity removal. Only one denitrification is required to meet the requirements, reducing the burden of each process, and reducing the cost of lithium extraction and the difficulty of operation.
[0025] (3) The present invention uses ultrasonic enhancement to enhance leaching, which can reduce the leaching temperature, effectively improve the slag type, and solve the problems of high leaching slag rate, difficult slag filtration, heavy burden on the filtration process, and low lithium extraction rate. Ultrasonic enhancement leaching is used for leaching, combined with the effect of mechanical stirring, to enhance the leaching effect, thereby improving the lithium extraction rate and treatment efficiency of electrolytic aluminum waste. The leaching rate of lithium in one stage can reach more than 97%, the leaching conditions are mild, and the treatment efficiency is high. At the same time, controlling the acidity of the leachate also inhibits the leaching of elements such as aluminum, sodium, iron, and fluorine. The burden of impurity removal of the leachate is greatly reduced, the amount of impurity removal slag is small, and the large amount of lithium loss caused by the adsorption of lithium by aluminum hydroxide in a colloidal state during alkali removal is reduced. The lithium loss is low, and the purity of battery-grade lithium carbonate products is easy to control.
[0026] (4) The lithium leaching solution of the present invention is subjected to two-stage impurity removal, wherein the first stage removes iron and aluminum impurities, and the second stage removes other impurities such as manganese and calcium. The main products of the two stages of impurity removal are different and are processed separately. In the two-stage impurity removal process, oxalic acid is used as a decalcifying agent instead of conventional ion exchange resin, which can avoid the generation of excessive wastewater and the problem of easy scaling of ion exchange resin in sulfuric acid system, so that calcium can be removed efficiently and the system operates smoothly.
[0027] (5) Since the aluminum content in the material is very high, the concentration of sodium ions in the lithium solution can be reduced to less than 20% of the original after impurities are removed. The lithium concentration can be increased to about 15g / L through a low-temperature crystallization denitration process for lithium precipitation. The denitration rate is high, the lithium loss in the denitration process is small, and the lithium recovery rate is high; the byproduct sodium sulfate has a small output and is easy to handle. The lithium solution after denitration is used to prepare battery-grade lithium carbonate by conventional methods, which is simple in process and low in cost.
[0028] The method of the invention can effectively extract lithium from electrolytic aluminum waste to prepare battery-grade lithium carbonate. The main component of the leached slag is cryolite, which can be utilized with good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0030] Figure 1 The process flow chart of the present invention is shown. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] A method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement, comprising the following steps:
[0033] Step 1: Use a crusher or manually crush the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content. The size of the crushed electrolytic aluminum waste is 1-10 cm; the composition and mass proportion of the electrolytic aluminum waste are: lithium 1%-1.2%, aluminum 12.5-12.8%, sodium 11.5-11.9%, iron 0.8-0.9%, calcium 1.8-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
[0034] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of no more than 80 meshes to obtain a decarbonized material;
[0035] Step 3: subject the decarbonized material to sulfuric acid leaching, subject the material to ultrasonic vibration during the sulfuric acid leaching process, adjust the leaching pH value to 3.0-4.0, the ultrasonic power is 500-2000W, obtain the leaching solution and leaching residue after filtering, the leaching residue is filtered and washed twice before storage, and the leaching residue washing water is returned to the leaching process; the slurry liquid-solid ratio of water to the decarbonized material in the leaching process is 3-5:1, the sulfuric acid is 98% sulfuric acid, the leaching temperature is 60-90°C, and the leaching time is 1-3h. The leaching kettle is connected to the absorption device, and the absorption liquid in the absorption device is a dilute alkali solution, which absorbs the fluorine and acid mist generated during the leaching process.
[0036] 2LiF+H2SO4→Li2SO4+2HF↑
[0037] 2Na3AlF6+6H2SO4→3Na2SO4+Al2(SO4)3+6HF↑
[0038] Fe+H2SO4→FeSO4+H2↑
[0039] Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the first stage leaching solution, and then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, oxygen, the impurity removal temperature is 55-70° C., the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5 hours;
[0040] 2FeSO4+H2SO4+H2O2→Fe2(SO4)3+2H2O (chemical equation with hydrogen peroxide as oxidant)
[0041] Al2(SO4)3+6NaOH→3Na2SO4+2Al(OH)3↓
[0042] Fe2(SO4)3+6NaOH→3Na2SO4+2Fe(OH)3↓
[0043] The second stage impurity removal process is: add decalcifying agent oxalic acid to the filtrate, then add alkali to adjust the pH value to 12.0-13.0, and filter to obtain lithium-containing filtrate and impurity filter residue; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is, and the amount of decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
[0044] Mn 2+ +2NaOH→2Na + +Mn(OH)2↓
[0045] H2C2O4+Ca 2+ →CaC2O4↓+2H +
[0046] Mg 2+ +2NaOH→2Na + +Mg(OH)2↓
[0047] Step 5: Heat and concentrate the lithium-containing filtrate, and then perform a freeze crystallization to obtain a denitrified liquid; the freeze crystallization temperature is -10°C-10°C to remove sodium sulfate.
[0048] Step 6: Add sodium carbonate solution to the denitrified liquid under heating conditions, and filter the precipitate to obtain crude lithium carbonate; the heating temperature is 90-100°C.
[0049] Li2SO4+Na2CO3→Li2CO3↓+2Na2SO4
[0050] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it accurately to obtain a lithium carbonate solution. Heat it for crystallization, filter it, wash it, and dry it to obtain battery-grade lithium carbonate. The mass ratio of pure water to crude lithium carbonate is 9-10:1, the pressure of the CO2 gas introduced is 0.1-0.2MPa, and the temperature of heating crystallization is 90-100℃.
[0051] The specific embodiments are as follows:
[0052] The electrolytic aluminum scrap used in the following examples is in the form of hard blocks, contains nearly half of the carbon, and the main components of the material are shown in Table 1.
[0053] Table 1 Composition and content of electrolytic aluminum waste
[0054]
[0055] Example 1
[0056] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0057] (2) Weigh 4000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a temperature of 700°C for 5 hours. Cool it to room temperature, take out the material and crush it into small pieces smaller than 80 mesh.
[0058] (3) The material after carbon removal is added to an ultrasonic enhanced reactor with a slurry liquid-solid ratio of 5:1 with water. An ultrasonic generator is installed in the reactor with an ultrasonic power of 1000W. The heating and stirring are turned on at the same time. The reactor is heated to 60°C for leaching. 98% sulfuric acid is added to adjust the pH value to 3.5. The leaching temperature is 60°C and the leaching is carried out for 2 hours. The leaching is filtered after leaching. The leaching liquid and leaching residue are obtained after filtration. The leaching residue is washed twice and then stored. The washing water of the leaching residue is returned to the leaching reactor. The leaching reactor is connected to an absorption device. The absorption liquid is a dilute alkali solution to absorb the HF gas generated during the leaching process. The lithium leaching rate is 98.08%, the iron leaching rate is 35.34%, and the aluminum leaching rate is 2.10%.
[0059] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: 1.2 times the theoretical amount of hydrogen peroxide is added to the leachate, followed by 5% sodium hydroxide to adjust the pH value to 4.5, the reaction temperature is maintained at 60°C, the reaction time is 4 hours, the filtrate and filter residue are obtained by filtration, the filter residue is slurried and washed twice, the filtrate is subjected to two-stage impurity removal, 2g of decalcifying agent is added, and then 5% sodium hydroxide is added to adjust the pH value to 12.5, the reaction time is 3 hours, the lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0060] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to 0°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0061] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 90°C to precipitate crude lithium carbonate.
[0062] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.1 MPa, and accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. Heat the lithium solution to a slightly boiling temperature (90-100°C) for crystallization, filter, wash, and dry to obtain battery-grade lithium carbonate.
[0063] Example 2
[0064] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0065] (2) Weigh 1000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a calcination temperature of 1000°C for 3 hours. Cool it to room temperature, take out the material and ball-mill it to 80 mesh.
[0066] (3) The material after carbon removal is added to an ultrasonic enhanced reactor with a slurry liquid-solid ratio of 5:1 with water. An ultrasonic generator is installed in the reactor with an ultrasonic power of 500 W. The heating and stirring are turned on at the same time. The material is heated to 55°C for leaching. 98% sulfuric acid is added to adjust the pH value to 3.0. The leaching temperature is 65°C and the leaching is carried out for 2 hours. The material is filtered after leaching to obtain the leachate and leaching residue. The leaching residue is washed twice and then stored. The washing water of the leaching residue is returned to the leaching reactor. The leaching reactor is connected to an absorption device. The absorption liquid is a dilute alkali solution to absorb the HF gas generated during the leaching process. The lithium leaching rate is 98.22%, the iron leaching rate is 35.34%, and the aluminum leaching rate is 2.10%. The leaching rate of iron and aluminum is greatly reduced by high pH leaching. The impurity content in the leachate is low, less acid is used for leaching, less alkali is used for impurity removal, less amount of crystallized sodium sulfate is used, the number of crystallizations is reduced, and the process is shortened.
[0067] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: 1.1 times the theoretical amount of sodium chlorate is added to the leachate, followed by 10% sodium hydroxide to adjust the pH value to 4.5, the reaction temperature is maintained at 70°C, the reaction time is 2 hours, the filtrate and filter residue are obtained by filtration, the filter residue is slurried and washed twice, the filtrate is subjected to two-stage impurity removal, 1 g of decalcifying agent is added, and then 10% sodium hydroxide is added to adjust the pH value to 12.0, the reaction time is 5 hours, the lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0068] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to 10°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0069] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 95°C to precipitate crude lithium carbonate.
[0070] (7) Add 9 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa. After all the lithium carbonate is dissolved, fine filtration is performed to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0071] Example 3
[0072] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0073] (2) Weigh 15,000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a temperature of 1,600°C for 5 hours. Cool it to room temperature, take out the material and ball-mill it into small pieces of 70 mesh.
[0074] (3) The decarbonized material is added to an ultrasonic enhanced reactor with a slurry liquid-solid ratio of 3:1 with water. An ultrasonic generator is installed in the reactor with an ultrasonic power of 2000W. The heating and stirring are turned on at the same time. The leaching is heated to 65°C and leaching is carried out. 98% sulfuric acid is added to adjust the pH value to 4.0. The leaching temperature is 65-70°C and the leaching is carried out for 3 hours. The leaching is filtered after leaching to obtain the leaching liquid and leaching residue. The leaching residue is washed twice and then stored. The washing water of the leaching residue is returned to the leaching process. The leaching reactor is connected to an absorption device. The absorption liquid is a dilute alkali solution to absorb the HF gas generated during the leaching process. The lithium leaching rate is 98.03%, the iron leaching rate is 35.34%, and the aluminum leaching rate is 2.10%.
[0075] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: oxygen is introduced into the leachate to oxidize all the divalent iron in the lithium solution into trivalent iron, and then 20% sodium hydroxide is added to adjust the pH value to 4.5. The reaction temperature is maintained at 65° C. The reaction time is 5 h. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. After 10 g of decalcifying agent is added, 20% sodium hydroxide is added to adjust the pH value to 13.0. The reaction time is 2 h. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0076] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to -10°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0077] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 98°C to precipitate crude lithium carbonate.
[0078] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa, and then accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0079] Table 2 Composition of the final lithium carbonate product in the embodiment
[0080]
[0081] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement, characterized in that: The following steps are involved: Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content; Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of no more than 80 meshes to obtain a decarbonized material; Step 3: subjecting the decarbonized material to sulfuric acid leaching, subjecting the material to ultrasonic vibration and mechanical stirring during the sulfuric acid leaching process, adjusting the leaching pH value to 3.0-4.0, the ultrasonic power to 500-2000W, and filtering to obtain the leaching solution and leaching residue; Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the second stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, filtering to obtain a lithium-containing filtrate and an impurity filter residue; Step 5: The lithium-containing filtrate is heated and concentrated, and then subjected to a freezing crystallization step to obtain a denitrified liquid; Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate; Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
2. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: The composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 12.5-12.8%, sodium 11.5-11.9%, iron 0.8-0.9%, calcium 1.8-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
3. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: The size of the electrolytic aluminum scrap after crushing in step 1 is 1-10 cm.
4. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: In step 3, the slurry liquid-solid ratio of water to carbon removal material in the leaching process is 3-5:1, the sulfuric acid is 98% sulfuric acid, the leaching temperature is 60-90° C., and the leaching time is 1-3 hours.
5. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: In step 4, the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, and oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
6. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: The temperature of the freezing crystallization in step 5 is -10°C to 10°C.
7. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhanced extraction according to claim 1, characterized in that: The heating temperature in step 6 is 90-100°C.
8. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhanced extraction according to claim 1, characterized in that: In step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2MPa.
9. The method for extracting lithium from electrolytic aluminum waste by ultrasonic enhancement according to claim 1, characterized in that: The temperature of heating crystallization in step 7 is 90-100°C.
Citation Information
Cited By
Method for selectively extracting magnesium and lithium components in aluminum alloy waste and co-producing graphene
CN120006100A